2016
DOI: 10.1016/j.molcel.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The K48-K63 Branched Ubiquitin Chain Regulates NF-κB Signaling

Abstract: Polyubiquitin chains of different topologies regulate diverse cellular processes. K48- and K63-linked chains, the two most abundant chain types, regulate proteolytic and signaling pathways, respectively. Although recent studies reported important roles for heterogeneous chains, the functions of branched ubiquitin chains remain unclear. Here, we show that the ubiquitin chain branched at K48 and K63 regulates nuclear factor κB (NF-κB) signaling. A mass-spectrometry-based quantification strategy revealed that K48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
213
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(232 citation statements)
references
References 37 publications
(64 reference statements)
8
213
0
Order By: Relevance
“…Such experiments suggested that M1/K63-linked chains control NFκB transcription factor activation (Emmerich et al, 2016; Emmerich et al, 2013; Wertz et al, 2015), while K11/K48-branched chains signal the degradation of cell cycle regulators during mitosis (Meyer and Rape, 2014). Similar in vitro or protein engineering evidence exists for K48/K63-branched, K29/K48-linked or more complex heterotypic chains (Kim et al, 2007; Koegl et al, 1999; Kristariyanto et al, 2015; Liu et al, 2017; Ohtake et al, 2016). These findings implied that cells use heterotypic chains for signal transduction, yet without a method to monitor endogenous polymers in vivo , the abundance, function, and importance of mixed or branched ubiquitin chains remain very poorly understood.…”
Section: Introductionmentioning
confidence: 63%
“…Such experiments suggested that M1/K63-linked chains control NFκB transcription factor activation (Emmerich et al, 2016; Emmerich et al, 2013; Wertz et al, 2015), while K11/K48-branched chains signal the degradation of cell cycle regulators during mitosis (Meyer and Rape, 2014). Similar in vitro or protein engineering evidence exists for K48/K63-branched, K29/K48-linked or more complex heterotypic chains (Kim et al, 2007; Koegl et al, 1999; Kristariyanto et al, 2015; Liu et al, 2017; Ohtake et al, 2016). These findings implied that cells use heterotypic chains for signal transduction, yet without a method to monitor endogenous polymers in vivo , the abundance, function, and importance of mixed or branched ubiquitin chains remain very poorly understood.…”
Section: Introductionmentioning
confidence: 63%
“…As prior studies have illustrated numerous roles of Lys63-linked (K63) polyubiquitylation in immune responses [39][40][41][42][43][44][45], as well as its relationship with Cbl-b [27], we determined if the deficiency in this E3 ubiquitin ligase could be associated with an abnormal polyubiquitin profile of T regs from SLE patients in a K63-dependent manner. According to our hypothesis, we observed a differential polyubiquitination profile distinguished by a decreased expression of K63 substrates in lupus T regs , but not in effector T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lysine-63-specific protein ubiquitination has been implicated in the regulation of signal transduction in immune receptors [39][40][41][42][43][44][45], which is mediated by the E2 ubiquitinconjugating enzyme Ubc13, as shown by multiple studies, and directs conjugated proteins to lysosomes [44]. As Ubc13 inducible knock-out mice specific for T regs display a reminiscent pathological phenotype of the T reg -deficient mice [46], we hypothesized that Cbl-b deficiency would modify the ubiquitin profile of T regs from SLE patients in a K63-dependent manner, which could contribute to resistance to suppression.…”
Section: Cd25mentioning
confidence: 99%
“…Ubiquitin itself has 7 lysine residues (K6, K11, K27, K29, K33, K48, and K63) along with its N-terminal methionine, resulting in the potential for multiple types of ubiquitin chains. Some of these linkages can be monomeric, polymeric, linked in tandem, branched, or even unanchored, with homogeneous or heterogeneous types of linkages [22,27,28]. In contrast to phosphorylation, multiple types of ubiquitin chains can be constructed and added to target proteins, which dramatically increases the amount of signaling information that can be encoded by ubiquitination.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to reiterate that different ubiquitin linkages lead to different outcomes for target proteins. K48- and K63-linked chains are the most abundant linkages in cells and are also the most extensively characterized [22,29]. K48-linked polyubiquitin chains generally direct target proteins to the proteasome for degradation [22].…”
Section: Introductionmentioning
confidence: 99%